FUNGSI KEPALA DESA DALAM PEMBERDAYAAN MASYARAKAT DI DESA KELAPA DUA KECAMATAN SELAT PENUGUAN KABUPATEN BANYUASIN - Tarmizi Endrianto (STIA SATYA NEGARA PALEMBANG, 2022)
Community empowerment carried out by the government is an alternative to reduce poverty. Thus the breadth and complexity of the problems that exist in Kelapa Dua Village, such as efforts to improve community welfare. Plus the procurement of development that must be carried out by the Kelapa Dua Village government to increase satisfaction, comfort in service to the community.The purpose of this research is basically to know the role of the village head in empowering the community of Kelapa Dua Village, Selat Penuguan District, Banyuasin Regency. In this study, the author uses qualitative research. In this study, the informants consisted of 7 people. The data analysis technique used in this research is qualitative data analysis technique.After doing the research, the findings show that. From the results of the research in the previous chapter, it can be concluded that the Head of Kelapa Dua Village has played a role in empowering the community of Kelapa Dua Village, Penuguan Strait District, Banyuasin Regency. As for what can be suggested to the village head, the role of the village head in community empowerment should be even better, so that the community empowerment program in Kelapa Dua village is growing. Keywords: The Functions Of The Village Hea, Community Empowerment